Analysis and Verification of Phase Current Detection Method of Permanent Magnet Synchronous Motor Based on Three Sampling Resistors Configuration. Issue 1 (1st November 2022) - Zhu, Ziwei; Cao, Jiayong; Ma, Qianli; Li, Fazhe
Abstract: In the permanent magnet synchronous motor (PMSM) control system, the phase current sampling unit is an important part of the whole motor control system. Traditionally, the hall-effect components are used to detecting the phase currents of the PMSM. However, the size of the hardware with Hall-effect components are often large. In this paper, a scheme of detecting the phase currents of PMSM by using three sampling resistors on the main circuit was discussed. In order to overcome the phenomenon that phase currents flow discontinuously across the three sampling resistors, a method for reconstructing the phase currents was proposed. Both simulation results and experimental results show that the phase currents can be reconstructed successfully and the high sampling accuracy can be obtained.